Promoting Heart Health Among Rural African Americans. Issue 1 (January 2018) - Abbott, Laurie; Williams, Christine; Slate, Elizabeth; Gropper, Sareen
Abstract : Background: Cardiovascular disease is a major cause of death for people living in the United States. African Americans bear a disproportionate burden of cardiovascular disease. Interventions designed to target multiple risk factors may facilitate elimination of cardiovascular disease health disparities. Objective: The purpose of this study was to evaluate a culturally relevant cardiovascular health promotion intervention that could potentially reduce cardiovascular disease risk among a group of rural African American adults by improving intentions, attitudes, norms, and self-efficacy to increase produce consumption, reduce dietary saturated fat intake, and increase exercise. Methods: A cluster randomized controlled trial design was used to evaluate the effect of the "With Every Heartbeat Is Life" cardiovascular health promotion program among rural African Americans. The African American congregants of 12 rural churches located in northern Florida were randomly assigned to either an intervention group that received a culturally relevant cardiovascular health promotion intervention or a control group. Data analysis using linear mixed model was performed to compare group differences from pretest to posttest. Results: The cardiovascular health promotion intervention had a positive influence on the intentions, attitudes, norms, and self-efficacy of rural African Americans to increase produce consumption and reduce dietary saturated fat. The intervention also enhanced participants' attitudes and self-efficacy regarding exercise. Conclusion: The culturally relevant cardiovascular health promotion program presented to cluster groups of rural African American participants had positive influences on psychosocial variables associated with engaging in cardiovascular health recommendations. Nurse-led interventions in community settings can potentially reduce cardiovascular disease risk.